2013
DOI: 10.1590/s1679-62252013000400014
|View full text |Cite
|
Sign up to set email alerts
|

Habitat characteristics and environmental parameters influencing fish assemblages of karstic pools in southern Mexico

Abstract: Fish assemblage structure was evaluated and compared among 36 karstic pools located within protected areas of the Calakmul Biosphere Reserve (southern Mexico) and unprotected adjacent areas beyond the Reserve. Nonmetric multidimensional scaling (MDS), indicator species analysis (ISA), and canonical correspondence analysis (CCA) were used to identify which environmental factors reflected local influences and to evaluate the correlation of these variables with fish assemblages structure. Thirty-one species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Nonetheless, the presence of widespread species in both species complexes clearly indicates a high potential for dispersal even across major phylogeographic barriers. For example, both P. sphenops and P. mexicana occur on both the Atlantic and Pacific slopes, and their ability for dispersal and colonization of novel habitats may be mediated by high tolerance to environmental stress (see Hernández-Rodríguez and Bückle-Ramirez, 2010;Tobler et al 2009;Trexler, 1986;Vega-Cendejas et al, 2013).…”
Section: Biogeographical Patterns Of Diversificationmentioning
confidence: 99%
“…Nonetheless, the presence of widespread species in both species complexes clearly indicates a high potential for dispersal even across major phylogeographic barriers. For example, both P. sphenops and P. mexicana occur on both the Atlantic and Pacific slopes, and their ability for dispersal and colonization of novel habitats may be mediated by high tolerance to environmental stress (see Hernández-Rodríguez and Bückle-Ramirez, 2010;Tobler et al 2009;Trexler, 1986;Vega-Cendejas et al, 2013).…”
Section: Biogeographical Patterns Of Diversificationmentioning
confidence: 99%
“…From these rivers, maximum level of fish abundance was detected at low water temperature and small flowing discharge in winter but minimum fish diversity viewed with comparatively high temperature and water discharge in summer differed by Yan et al (2010) due to geographical variation. Alteration in water quality parameters such as water temperature, dissolved oxygen, pH, transparency and depth influence the uniqueness of aquatic environment and fish breeding (Kathiresan and Bingham, 2001;Rashleigh, 2004), profusion and allotment (Maes et al, 2004), migration and distribution (Vega-Cendejas et al, 2013) and survival of fishes (Whitfield, 1999) ultimately altering fish assemblage and structure. However, significant differences (P < 0.05) were observed in hydrological parameters among habitat and season similar to Grimaldo et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…In freshwater habitat of south Florida's Everglades National Park, Kerfoot et al [37] found a positive relationship between pH (range:~7.4-8.0) and B. belizanus density at one site, a weak positive relationship at another site (pH range:~7.2-7.4), and negative relationships at two other sites (pH ranges:~7.3-7.6 and~7.6-8.1). Multispecies ordination analyses within the native range do not demonstrate strong or consistent relationships between pH and B. belizanus populations [33][34][35][36]. As noted by Kerfoot et al [37], changes in pH are known to directly affect ion uptake across gills and internal acid-base balance in fishes, ultimately affecting survival rates.…”
Section: Habitat Predictabilitymentioning
confidence: 93%